2020
DOI: 10.1021/acssuschemeng.9b06555
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Threshold Pressure of Reversibly Sigmoidal NH3 Absorption Isotherm with Ionic Liquids

Abstract: In this work, flexible hydrogen-bonded frameworks composed of amino pyridinium-based protic ionic liquids (ILs) marked as [X-PyH]­[Tf2N] were designed as NH3 absorption agents. Interestingly, NH3 absorption isotherm of these ILs present sigmoidal absorption isotherm (S mode), and the threshold pressure (TP) decreases from 75 to 6 mbar with the tunable of hydrogen bonded frameworks by varying the substituted group X. Combined with XRD characterizations, Fourier transform infrared and 1H NMR spectroscopies, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Qiu et al further demonstrated that the threshold pressure of sigmoidal NH 3 absorption can be much reduced through tuning the chemical structures of protonated ILs, which is very useful for the absorption of NH 3 at low pressure. 34 Hydroxyl groups were previously introduced into the chemical structures of ILs to improve the physical absorption of NH 3 , because they enable a hydrogen-bond interaction with NH 3 . Cai et al designed a series of Li-triethylene glycol (TEG) chelated ILs with a crown-ether-like cation and different anions for NH 3 absorption.…”
Section: Liquid Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu et al further demonstrated that the threshold pressure of sigmoidal NH 3 absorption can be much reduced through tuning the chemical structures of protonated ILs, which is very useful for the absorption of NH 3 at low pressure. 34 Hydroxyl groups were previously introduced into the chemical structures of ILs to improve the physical absorption of NH 3 , because they enable a hydrogen-bond interaction with NH 3 . Cai et al designed a series of Li-triethylene glycol (TEG) chelated ILs with a crown-ether-like cation and different anions for NH 3 absorption.…”
Section: Liquid Absorptionmentioning
confidence: 99%
“…Thus, the capacities of NH 3 absorption were improved, and meanwhile the energy consumption of NH 3 desorption was decreased. Qiu et al further demonstrated that the threshold pressure of sigmoidal NH 3 absorption can be much reduced through tuning the chemical structures of protonated ILs, which is very useful for the absorption of NH 3 at low pressure …”
Section: Liquid Absorptionmentioning
confidence: 99%
“…In the past two decades, protic ionic liquids (ILs), ILs substituted with the hydrogen donor, , and ILs with the metallic anion were developed for efficient and reversible absorption of NH 3 . Deep eutectic solvents mixed with hydrogen-bond acceptors and various hydrogen-bond donors have been proposed as very promising NH 3 absorbents through Lewis acid–base interaction and hydrogen-bonding interaction by taking advantage of the essence of ammonia as a Lewis base and a hydrogen acceptor .…”
Section: Introductionmentioning
confidence: 99%
“…18 Liu et al found that protic ILs could serve as efficient catalysts for the synthesis of quinazoline-2,4(1 H ,3 H )-dione with 97% yield at room temperature and atmospheric pressure. 15 Beside CO 2 capture and conversion, ILs could also be favourable media for biomass utilization, 26 SO 2 uptake, 27 NO x absorption, 28 NH 3 separation 8,29–31 and lithium-ion batteries recovery. 32…”
Section: Introductionmentioning
confidence: 99%